Single‐Atom Reversible Lithiophilic Sites toward Stable Lithium Anodes. Issue 8 (12th January 2022) - Yang, Zhilin; Dang, Yan; Zhai, Pengbo; Wei, Yi; Chen, Qian; Zuo, Jinghan; Gu, Xiaokang; Yao, Yong; Wang, Xingguo; Zhao, Feifei; Wang, Jinliang; Yang, Shubin; et al.
Abstract: Lithiophilic sites with high binding energy to Li have shown the capability to guide uniform Li deposition, however, the irreversible reaction between Li and lithiophilic sites causes a loss of lithiophilicity. Herein, the concept of using reversible lithiophilic sites, such as single‐atoms (SAs) doped graphene, as a host, is systematically inspected in the context of Li metal battery (LMB) performance. Here, it is proposed that the binding energy to Li atoms should be within a certain threshold range, i.e., strong enough to inhibit Li dendrite growth and weak enough to avoid host structure collapse. Six kinds of SAs are utilized; doped 3D graphene, nitrogen‐doped 3D graphene, and pure 3D graphene, whose performance in LMBs are compared with each other. It is discovered that the SA‐Mn doped 3D graphene (SAMn@NG) has the most reversible lithiophilic site, in which adsorption strength with Li is suitable to guide uniform deposition and keep the structure stable. During Li plating/stripping, the changes of the atomic structures in SAMn@NG, such as change of bond length and bond angle around Mn atoms are much smaller than those on SAZr@NG, although its binding energy is higher, enabling a much‐improved battery performance in SAMn@NG. This work provides a new insight to design lithiophilic sites in LMBs. Abstract : In this work, the concept of using reversible lithiophilic sites, such as single‐atoms doped graphene, as a host is systematically inspected in the context of lithium metal battery performance. The binding energy to lithium atoms should be within a certain threshold range, i.e. strong enough to inhibit lithium dendrite growth and weak enough to avoid host structure collapse.